Genetic Manipulation of Neisseria gonorrhoeae - Dillard, Joseph P. (Curr Protoc Microbiol, 2011)
The sexually-transmitted pathogen, Neisseria gonorrhoeae, undergoes natural transformation at high frequency. This property has led to the rapid dissemination of antibiotic resistance markers and to the panmictic structure of the gonococcal population. However, high frequency transformation also makes N. gonorrhoeae one of the easiest bacterial species to manipulate genetically in the laboratory. Techniques have been developed that result in transformation frequencies >50%, allowing the identification of mutants by screening and without selection. Constructs have been created to take advantage of this high frequency transformation, facilitating genetic mutation, complementation, and heterologous gene expression. Techniques are described for genetic manipulation of N. gonorrhoeae, as well as for growth of this fastidious organism.